Icariin Attenuates Monocrotaline-Induced Pulmonary Arterial Hypertension via the Inhibition of TGF-β1/Smads Pathway in Rats. (1st December 2020) - Xiang, Yijia; Cai, Changhong; Wu, Yonghui; Yang, Lebing; Ye, Shiyong; Zhao, Huan; Zeng, Chunlai
Abstract : Background . Pulmonary artery remodeling is important in the development of pulmonary artery hypertension. The TGF- β 1/Smads signaling pathway is activated in pulmonary arterial hypertension (PAH) in rats. Icariin (ICA) suppresses the TGF- β 1/Smad2 pathway in myocardial fibrosis in rats. Therefore, we investigated the role of icariin in PAH by inhibiting the TGF- β 1/Smads pathway. Methods . Rats were randomly divided into control, monocrotaline (MCT), MCT + ICA-low, and MCT + ICA-high groups. MCT (60 mg/kg) was subcutaneously injected to induce PAH, and icariin (50 or 100 mg/kg.d) was orally administered for 2 weeks. At the end of the fourth week, right ventricular systolic pressure (RVSP) was obtained and the right ventricular hypertrophy index (RI) was determined as the ratio of the right ventricular weight to the left ventricular plus septal weight (RV/LV + S). Western blots were used to determine the expression of TGF- β 1, Smad2/3, P-Smad2/3, and matrix metalloproteinase-2 (MMP2) in lung tissues. Results . Compared to the control group, RVSP and RI were increased in the MCT group ( ρ < 0.05). Additionally, TGF- β 1, Smad2/3, P-Smad2/3, and MMP2 expressions were obviously increased ( ρ < 0.01). Compared to the MCT group, RVSP and RI were decreased in the MCT + ICA group ( ρ < 0.05). TGF- β 1, Smad2/3, P-Smad2/3, and MMP2 expressions were also inhibited in the icariin treatment groups ( ρ < 0.05) . Conclusions . Icariin may suppress MCT-induced PAH via the inhibition of the TGF β 1-Smad2/3 pathway.